Ouragans et submersions dans les Antilles françaises (xviie - xxe siècle) - Jérémy Desarthe (Études Caribéennes)
The rising vulnerability to Extreme hazard and the consequences of climate change increase the exposure of French Antilles to natural hazards. Therefore, the French reinsurance company Caisse Centrale de Réassurance aims to develop its scientific knowledge of hurricanes and induced phenomena like storm surges, floods and landslides.With the study of historical archives, located in the Antilles and Metropolitean France, it was possible to build an exhaustive hurricane Severity chronology since the 17th century. Then, a detailed damage analysis in specific strategic areas has offered the opportunity to assess the evolution of the vulnerability of the French Antilles societies. Furthermore, the Risk Management policies, since the 17th century, attest the willingness to protect strategic areas and populations and highlight the link between risk and land use.